Automatic Construction Method of Topological Map of Obstacles in Mining Area - Yan Huang, Ruifeng Tian, Yu Xia (Forest Chemicals Review, 1970)
Constructing obstacle map is a necessary step before unmanned driving system carries out path planning. Aiming at the application of autonomous driving in mining area, the author proposed a fast method of constructing obstacle topological map, providing route planning map information for autonomous vehicles. Considering the practical problems of obstacles in mining scenes, such as goods, vehicles and people, change frequently, this paper first constructs a prior map, then fuses the obstacle map in real-time positioning, and constructs a topological map based on the fused map for path planning.